2019
DOI: 10.3390/s19081774
|View full text |Cite
|
Sign up to set email alerts
|

Prediction and Decision-Making in Intelligent Environments Supported by Knowledge Graphs, A Systematic Review

Abstract: Ambient Intelligence is currently a lively application domain of Artificial Intelligence and has become the central subject of multiple initiatives worldwide. Several approaches inside this domain make use of knowledge bases or knowledge graphs, both previously existing and ad hoc. This form of representation allows heterogeneous data gathered from diverse sources to be contextualized and combined to create relevant information for intelligent systems, usually following higher level constraints defined by an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 79 publications
0
7
0
Order By: Relevance
“…For example, ZAR [20] used the coe cient in biological studies. Additionally, Amador-Domínguez [21] have used it in the eld of arti cial intelligence. Kirch [22] described Pearson's correlation coe cient (Rho) as the measure of the linear similarity between two variables.…”
Section: Discussionmentioning
confidence: 99%
“…For example, ZAR [20] used the coe cient in biological studies. Additionally, Amador-Domínguez [21] have used it in the eld of arti cial intelligence. Kirch [22] described Pearson's correlation coe cient (Rho) as the measure of the linear similarity between two variables.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, exploring the interpretability and explainability of the machine learning models used is essential. As shown in a recent review [ 45 ], most prediction and decision-making methods in intelligent environments are interpretable. Therefore, the use of grey-box models, which combine the interpretability of a white-box model with the accuracy of a black-box model, will be considered [ 40 ].…”
Section: Conclusion and Future Workmentioning
confidence: 99%
“…While few existing studies [36]- [38] have demonstrated the promise of utilising KGs for systematically structuring conceptual information in the wind industry, they only serve as an end point [39] providing information for consultation without the ability to further reason over the data. Moreover, these ontologies need to be queried manually through specialised graph query languages to extract relevant and meaningful information, which may not be easily accessible to turbine engineers & technicians.…”
Section: Introductionmentioning
confidence: 99%